Aldehyde dehydrogenase 2 activation and coevolution of its εPKC-mediated phosphorylation sites. Issue 1 (December 2017) - Nene, Aishwarya; Chen, Che-Hong; Disatnik, Marie-Hélène; Cruz, Leslie; Mochly-Rosen, Daria
Abstract Background Mitochondrial aldehyde dehydrogenase 2 (ALDH2) is a key enzyme for the metabolism of many toxic aldehydes such as acetaldehyde, derived from alcohol drinking, and 4HNE, an oxidative stress-derived lipid peroxidation aldehyde. Post-translational enhancement of ALDH2 activity can be achieved by serine/threonine phosphorylation by epsilon protein kinase C (εPKC). Elevated ALDH2 is beneficial in reducing injury following myocardial infarction, stroke and other oxidative stress and aldehyde toxicity-related diseases. We have previously identified three εPKC phosphorylation sites, threonine 185 (T185), serine 279 (S279) and threonine 412 (T412), on ALDH2. Here we further characterized the role and contribution of each phosphorylation site to the enhancement of enzymatic activity by εPKC. Methods Each individual phosphorylation site was mutated to a negatively charged amino acid, glutamate, to mimic a phosphorylation, or to a non-phosphorylatable amino acid, alanine. ALDH2 enzyme activities and protection against 4HNE inactivation were measured in the presence or absence of εPKC phosphorylation in vitro. Coevolution of ALDH2 and its εPKC phosphorylation sites was delineated by multiple sequence alignments among a diverse range of species and within the ALDH multigene family. Results We identified S279 as a critical εPKC phosphorylation site in the activation of ALDH2. The critical catalytic site, cysteine 302 (C302) of ALDH2 is susceptible to adduct formation by reactive aldehyde, 4HNE, which readily renders the enzyme inactive. We show that phosphomimetic mutations of T185E, S279E and T412E confer protection of ALDH2 against 4HNE-induced inactivation, indicating that phosphorylation on these three sites by εPKC likely also protects the enzyme against reactive aldehydes. Finally, we demonstrate that the three ALDH2 phosphorylation sites co-evolved with εPKC over a wide range of species. Alignment of 18 human ALDH isozymes, indicates that T185 and S279 are unique ALDH2, εPKC specific phosphorylation sites, while T412 is found in other ALDH isozymes. We further identified three highly conserved serine/threonine residues (T384, T433 and S471) in all 18 ALDH isozymes that may play an important phosphorylation-mediated regulatory role in this important family of detoxifying enzymes. Conclusion εPKC phosphorylation and its coevolution with ALDH2 play an important role in the regulation and protection of ALDH2 enzyme activity.